Can Institutional Reform Reduce Job Destruction and Unemployment Duration? : Yes it Can - Perez Ruiz, Esther; Yao, Yao. (Washington, D.C. : International Monetary Fund, 2012)
We read search theory's unemployment equilibrium condition as an Iso-Unemployment Curve(IUC).The IUC is the locus of job destruction rates and expected unemployment durations rendering the same unemployment level. A country's position along the curve reveals its preferences over the destruction-duration mix, while its distance from the origin indicates the unemployment level at which such preferences are satisfied Using a panel of 20 OECD countries over 1985-2008, we find employment protection legislation to have opposing efects on destructions and durations, while the effects of the remaining key institutional factors on both variables tend to reinforce each other. Implementing the right reforms could reduce job destruction rates by about 0.05 to 0.25 percentage points and shorten unemployment spells by around 10 to 60 days. Consistent with this, unemployment rates would decline by between 0.75 and 5.5 percentage points, depending on a country's starting position.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet